1997
DOI: 10.1093/ije/26.6.1151
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences and factors related to breast cancer survival in Hawaii

Abstract: Despite an overall improvement in breast cancer survival, ethnic disparity in prognosis still exists. Other possible explanations for the differential prognosis, such as treatment, diet, genetics, obesity, oestrogen receptor and hormonal statuses need to be explored in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 25 publications
4
46
0
4
Order By: Relevance
“…Whereas others have recently found no association between SES and breast cancer survival in Hawaii, the gradient most typical of other states (lower survival rates among the poor) was observed there in earlier cohorts from the 1960s through 1970s. 43,44 The previously observed pattern of advantaged Hawaiian cancer survival within the United States is also consistent with this study's findings. 45 It is possible-but, we think, improbable-that other factors may account for this study's findings.…”
Section: Discussionsupporting
confidence: 91%
“…Whereas others have recently found no association between SES and breast cancer survival in Hawaii, the gradient most typical of other states (lower survival rates among the poor) was observed there in earlier cohorts from the 1960s through 1970s. 43,44 The previously observed pattern of advantaged Hawaiian cancer survival within the United States is also consistent with this study's findings. 45 It is possible-but, we think, improbable-that other factors may account for this study's findings.…”
Section: Discussionsupporting
confidence: 91%
“…More than 5 year survival was 73% in premenopausal women and 76% in postmenopausal women. A study on breast cancer survival in Hawaii also found no association for menopausal status (Meng et al, 1997).…”
Section: 1019 Impact Of Tumour and Factors On Survival Of Breast Canmentioning
confidence: 96%
“…This is of particular concern for A/PI, H, and Other categories because subgroups within these categories (ie, Native American, Hawaiian, Mexican, South/Central American, Puerto Rican) have greater breast cancer mortality and poorer survival than white women. 4,44 The potential for underserved subgroups within the AA population also exists, with Caribbean women having a different screening profile than other women identified as AA. 45,46 Future analyses should disaggregate the R/E categories so that we can better understand these findings.…”
Section: Strengths/limitationsmentioning
confidence: 99%
“…45,46 Future analyses should disaggregate the R/E categories so that we can better understand these findings. 11,44 The use of aggregate-based measures to assign individual SES status is suboptimal. 20 However, aggregate measures of income at the community level remains valuable because community-level predictors of SES have been shown to be a strong predictor of healthcare services and health outcomes for all individuals living in that community (both high and low income).…”
Section: Strengths/limitationsmentioning
confidence: 99%